2018
DOI: 10.1007/s11936-018-0627-x
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Cardiovascular Toxicity: Mechanisms, Prevention, and Treatment

Abstract: Recent studies exploring the acute and chronic effects of radiation therapy on cardiac and vascular tissue have provided new insights into the development and progression of heart disease, including the identification and understanding of age- and complication-associated risk factors. However, key questions relating to the connection from upstream signaling to fibrotic changes remain. In addition, advances in the delivery of chest radiotherapy have helped to limit heart exposure and damage, but additional refi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 71 publications
0
51
0
Order By: Relevance
“…The removal of undesired or faulty cells by regulated cell death is a fundamental physiological process which is vital for development, immunity and tissue homeostasis. Furthermore, disruption of the programmed cell death pathways can lead to abnormally high or low rates of cell death, and is associated with many of the diseases that constitute the top causes of death worldwide, including cardiovascular, neurodegenerative, pulmonary, renal and hepatic diseases, as well as cancer (Goilav, 2011;Johnstone et al, 2002;Lozano et al, 2012;Lu et al, 2014;Okouchi et al, 2007;Spetz et al, 2018;Su et al, 1997;Wang, 2014;Whelan et al, 2010). Several different modes of programmed cell death have been described in the literature in numerous biological contexts, and the study of these pathways has been instrumental in explaining the diverse biological processes involved in cell loss (Galluzzi et al, 2018).…”
Section: Cell Death Pathways In T Cellsmentioning
confidence: 99%
“…The removal of undesired or faulty cells by regulated cell death is a fundamental physiological process which is vital for development, immunity and tissue homeostasis. Furthermore, disruption of the programmed cell death pathways can lead to abnormally high or low rates of cell death, and is associated with many of the diseases that constitute the top causes of death worldwide, including cardiovascular, neurodegenerative, pulmonary, renal and hepatic diseases, as well as cancer (Goilav, 2011;Johnstone et al, 2002;Lozano et al, 2012;Lu et al, 2014;Okouchi et al, 2007;Spetz et al, 2018;Su et al, 1997;Wang, 2014;Whelan et al, 2010). Several different modes of programmed cell death have been described in the literature in numerous biological contexts, and the study of these pathways has been instrumental in explaining the diverse biological processes involved in cell loss (Galluzzi et al, 2018).…”
Section: Cell Death Pathways In T Cellsmentioning
confidence: 99%
“…Moreover, the risk of cardiovascular complications in patients who received radiotherapy for left breast cancer was significantly higher than the risk in patients who received radiotherapy for right breast cancer [10]. Although the benefit of radiotherapy is obvious, increasing attention has been paid to the cardiac damage induced by radiotherapy, which would suggest limiting the dose and use of radiotherapy in cancer patients [11]. Modern radiotherapy techniques may not have decreased cardiac toxicity even though they have reduced the exposure of the heart to radiation [12].…”
Section: Introductionmentioning
confidence: 99%
“…Investigations into preventing and treating irradiation damage, drug efficacy, and mitigating the effects of irradiation on the pharmacokinetics of drugs, such as 5-fluorouracil, cisplatin, and irinotecan hydrochloride, have been conducted for years (Hsieh et al, 2011;Duan et al, 2015;Tsai et al, 2015;Spetz et al, 2018;Qiao et al, 2019). These studies have observed significant differences in the characteristics of drugs in experimental rats after irradiation exposure.…”
Section: Introductionmentioning
confidence: 99%